Using the Reputation Score Management for Constructing Fair P2P File Sharing System - Jun Han; Shufang Zhang (Institute of Advanced Engineering and Science, 2013)
This paper has used the reputation score management for constructing a fair P2P file sharing system, the system design principle is simple and easy to realize, and every node entering into the P2P network obtains a certain reputation score, and obtains the corresponding resources reward according to the score. This paper has described the fair sharing strategies facing node network bandwidth and TTL, and these strategies can be used independently or be combined with other reputation score managements of P2P network. These two strategies have been discussed in the specific reputation score management system of P2P network Eigen Trust, and the test results indicate that: compared with a common P2P network, the fair sharing strategies of this paper have faster file download speed and can decrease the network message communication amount during the process looking for resources. It can also be combined with another reputation management system. it is simple and easy to be realized, its main purposes are to fairly share network bandwidth and to decrease information communication volume, and it can suppress the free riding behavior to some extent. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2669